Role of Civil Community Institutions in Fighting Corruption - Abu Shari'ah, Hamzeh Ismaeil Ibrahim (Journal of Humanities and Social Sciences Studies, 2024)
The study aimed at showing the role of the civil community institutions in fighting corruption; meanwhile, the problem of the study centred on an axial question, meaning: how can the organizations of the civil community share in fighting corruption? To answer the question of the study and achieve its objectives, the descriptive analytical method was employed, and the study certifies that civil community institutions have a great role in fighting corruption. Also, the study deduced numerous deductions, the most important of which are the institutions of the civil community, which are considered the most significant in formal sectors of the state that work to consolidate security and stability in democratic communities and in fighting corruption. The study resulted in numerous recommendations, the most significant of which are participating in the institutions of the civil community in drawing the public policies considered the effective partner of the governments in fighting corruption and empowering the institutions of the civil community in having different media means to fight corruption.